A Comparison of Recreation Curriculum between United States of America and Turkey - Abdulmenaf Korkutata (Sakarya University Journal of Education)
The aim of this research is to examine comparatively the lessons at Recreation Department Education Programme at the universities in America and Turkey .Document analysis method, which is one of the qualitative search method, is used in the study.The datas of the study are gathered from the lessons including at the Recreation Department Education Programme of 5 Universities in America and Turkish which are established the best universities at University Ranking by Academic Performance in 2016.The findings got from the research are:1. Recreation takes part in the department related to health in America , on the other hand, in Turkey it takes part in the departments of Physical Education and Sport Institution 2.At Recreation Departments, General Culture and applied sport lessons take part in the USA mostly applied sport lessons and theoretical department knowledge take part in Turkey.3.Applied Department knowledge lessons takea part in the USA on the other hand the lessons about internship and health take part in Turkey.